Applications of solid phase microextraction - Pawliszyn, Janusz (Royal Society of Chemistry, 1999)
Solid Phase Microextraction (SPME) has been introduced as a modern alternative to current sample preparation technology, and has a wide range of applications. Focusing on quantitative aspects of analysis, Applications of Solid Phase Microextraction aims to describe these applications. In industry, practical uses of SPME can be found in environmental, food, pharmaceutical, clinical and forensic applications, all of which are described in this book. Important scientific applications such as reaction monitoring, characterization of coatings and distributions of analytes in natural multiphase systems are also discussed. Throughout there are descriptions of new technologies, including new coatings and interfaces for analytical instrumentation (SPME/LC and SPME/CE), automation and calibration processes. Written by internationally recognised experts, edited by the scientist involved in the research since its infancy, and encompassing a wide range of applications, this book will be ideal for anyone wishing to explore the feasibility of using SPME technology.
RSC chromatography monographs
Keywords: Chemistry Techniques, Analytical; chemické techniky analytické; chemie, klinická chemie